Could AMPs and B-cells be the missing link in understanding periodontitis? - Lobognon, Vanessa Dominique; Alard, Jean-Eric (Frontiers in Immunology, 2022)
Periodontal diseases are common inflammatory conditions characterized by bone loss in response to simultaneous bacterial aggression and host defences. The aetiology of such diseases is still not completely understood, however. It has been shown that specific pathogens involved in the build-up of dysbiotic biofilms participate actively in the establishment of periodontitis. This multifactorial pathology also depends on environmental factors and host characteristics, especially defences. The immune response to the pathogens seems to be critical in preventing the disease from starting but also contributes to tissue damage. It is known that small molecules known as antimicrobial peptides (AMPs) are key actors in the innate immune response. They not only target microbes, but also act as immuno-modulators. They can help to recruit or activate cells such as neutrophils, monocytes, dendritic cells or lymphocytes. AMPs have already been described in the periodontium, and their expression seems to be connected to disease activity. Alpha and beta defensins and LL37 are the AMPs most frequently linked to periodontitis. Additionally, leukocyte infiltrates, especially B cells, have also been linked to the severity of periodontitis. Indeed, the particular subpopulations of B cells in these infiltrates have been linked to inflammation and bone resorption. A link between B cells and AMP could be relevant to understand B cells action. Some AMP receptors, such as chemokines receptors, toll like receptors or purinergic receptors, have been shown to be expressed by B cells. Consequently, the action of AMPs on B cell subpopulations could participate to B cell recruitment, their differentiation and their implication in both periodontal defence and destruction.